Plasmodium falciparum dihydroartemisinin-piperaquine failures in Cambodia are associated with mutant K13 parasites presenting high survival rates in novel piperaquine in vitro assays: retrospective and prospective investigations. Issue 1 (December 2015) - Duru, Valentine; Khim, Nimol; Leang, Rithea; Kim, Saorin; Domergue, Anais; Kloeung, Nimol; Ke, Sopheakvatey; Chy, Sophy; Eam, Rotha; Khean, Chanra; Loch, Kaknika; Ken, Malen; et al.
Abstract Background The declining efficacy of dihydroartemisinin-piperaquine againstPlasmodium falciparum in Cambodia, along with increasing numbers of recrudescent cases, suggests resistance to both artemisinin and piperaquine. Available in vitro piperaquine susceptibility assays do not correlate with treatment outcome. A novel assay using a pharmacologically relevant piperaquine dose/time exposure was designed and its relevance explored in retrospective and prospective studies. Methods The piperaquine survival assay (PSA) exposed parasites to 200 nM piperaquine for 48 hours and monitored survival 24 hours later. The retrospective study tested 32 culture-adapted, C580Y-K13 mutant parasites collected at enrolment from patients treated with a 3-day course of dihydroartemisinin-piperaquine and having presented or not with a recrudescence at day 42 (registered ACTRN12615000793516). The prospective study assessed ex vivo PSA survival rate alongside K13 polymorphism of isolates collected from patients enrolled in an open-label study with dihydroartemisinin-piperaquine for uncomplicatedP. falciparum malaria in Cambodia (registered ACTRN12615000696594). Results All parasites from recrudescent cases had in vitro or ex vivo PSA survival rates ≥10 %, a relevant cut-off value for piperaquine-resistance. Ex vivo PSA survival rates were higher for recrudescent than non-recrudescent cases (39.2 % vs. 0.17 %, P <1 × 10−7 ). Artemisinin-resistant K13 mutants with ex vivo PSA survival rates ≥10 % were associated with 32-fold higher risk of recrudescence (95 % CI, 4.5–224;P  = 0.0005). Conclusion PSA adequately captures the piperaquine resistance/recrudescence phenotype, a mainstay to identify molecular marker(s) and evaluate efficacy of alternative drugs. Combined ex vivo PSA and K13 genotyping provides a convenient monitor for both artemisinin and piperaquine resistance where dihydroartemisinin-piperaquine is used.